2000
DOI: 10.1128/mcb.20.15.5469-5478.2000
|View full text |Cite
|
Sign up to set email alerts
|

The T-Cell Receptor Regulates Akt (Protein Kinase B) via a Pathway Involving Rac1 and Phosphatidylinositide 3-Kinase

Abstract: The serine/threonine kinase Akt (also known as protein kinase B) (Akt/PKB) is activated upon T-cell antigen receptor (TCR) engagement or upon expression of an active form of phosphatidylinositide (PI) 3-kinase in T lymphocytes. Here we report that the small GTPase Rac1 is implicated in this pathway, connecting the receptor with the lipid kinase. We show that in Jurkat cells, activated forms of Rac1 or Cdc42, but not Rho, stimulate an increase in Akt/PKB activity. TCR-induced Akt/PKB activation is inhibited eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(74 citation statements)
references
References 48 publications
8
66
0
Order By: Relevance
“…In line with our present results, whereas early work indicated that small G proteins of the Rho family do not play a role in Akt regulation (Klippel et al, 1996), more recent studies have shown that Rac1 and 2 can indeed activate Akt in cells of hematopoietic origin, such as Jurkat and BaF3 cells (Genot et al, 2000;Nishida et al, 1999). In T cells, Rac activation of Akt participates in the formation of membrane spikes (Genot et al, 2000), and in BaF3 cells in the viability upon IL-3 removal (Nishida et al, 1999).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In line with our present results, whereas early work indicated that small G proteins of the Rho family do not play a role in Akt regulation (Klippel et al, 1996), more recent studies have shown that Rac1 and 2 can indeed activate Akt in cells of hematopoietic origin, such as Jurkat and BaF3 cells (Genot et al, 2000;Nishida et al, 1999). In T cells, Rac activation of Akt participates in the formation of membrane spikes (Genot et al, 2000), and in BaF3 cells in the viability upon IL-3 removal (Nishida et al, 1999).…”
Section: Discussionsupporting
confidence: 81%
“…In T cells, Rac activation of Akt participates in the formation of membrane spikes (Genot et al, 2000), and in BaF3 cells in the viability upon IL-3 removal (Nishida et al, 1999). Furthermore, in Rac2-de®cient mast cells, the survival response to growth factors was diminished, and that correlated with a decreased activation of Akt and enhanced BAD/Bcl-X L expression .…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, Vav-1 has been shown to be required for the membrane targeting of PKC-(50). It was also suggested that PI3-K may act downstream of Rac-1, a downstream substrate of Vav-1 (9). Therefore, the relationship between PI3-K, Vav-1, and PKC-is still not fully defined.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that PI3-K may regulate the exchange activity of Vav-1 in vitro through its product phosphatidylinositol 3,4,5-trisphosphate (PIP 3 ), which binds to the PH domain of Vav-1 and recruits Vav-1 to the plasma membrane (10,30). However, it has also been reported that PI3-K may act downstream of Rac-1, a downstream substrate of Vav-1 (9). Therefore, the relationship among Vav-1, PI3-K, and PKC-in primary T cells is not fully characterized.…”
Section: Suppression Of Tcr-induced Pkc-activation By Cbl-b Requires mentioning
confidence: 97%
“…This result is consistent with a previous study arguing that PI3K is an effector of Rac GTPase rather than Ras in T cells. Hence, an overexpression of Ras V12C40 may not necessarily mimic physiological conditions that control PI3K function in these cells (27).…”
Section: Functional Phenotype Of Cd4 T Cells Transduced With Ras V12gmentioning
confidence: 99%